Enhancing Purchase Intention in tiktok Live-Stream: The Roles of Streamers’ Credibility, Interactivity, and Perceived Risk among Generation Z Buyers - Hamidah, Rusyda; Pangaribuan, Christian Haposan; Luhur, Calista (Jurnal Sosial Humaniora, 2024)
The growth of social media has had an impact on economic growth. One of these social media platforms is TikTok, which offers tools that facilitate the ability of users to conduct buying and selling transactions. TikTok offers a live-stream feature that makes it simpler for sellers to advertise their goods and allows customers to view and engage with sellers in real time. However, many TikTok users are less engaged in shopping through TikTok live-stream because of trust issues. Using the Stimulus-Organism-Response (S-O-R) theory, this thesis examines the impact of streamers’ credibility and interactivity on Generation Z TikTok buyers’ perceived risk and purchase intention in the context of live-stream e-commerce. This research was conducted in Indonesia. The study utilizes a quantitative research approach, collecting 127 data from Generation Z TikTok users through an online survey. Data analysis is conducted using statistical techniques to test research hypotheses. The findings indicate that streamers’ credibility significantly reduces perceived risk, while interactivity does not significantly influence it. Perceived risk, in turn, negatively affects purchase intention. Furthermore, streamers’ credibility and interactivity have a positive and significant direct effect on purchase intention. These results contribute to understanding consumer behavior in the context of TikTok live-stream e-commerce and have implications for marketers and researchers targeting Generation Z consumers.